Coordination of care in the context of primary brain tumors: Australian healthcare professionals’ exploration of the unspoken impact and clinical implications - Megan S. Jeon; Hannah Isaac; Joanne Shaw; Dianne M. Legge; Sharon He; Thomas Carlick; Eng-Siew Koh; Georgia K. B. Halkett; Brian Kelly; Mark B. Pinkham; Raymond J. Chan; Tamara Ownsworth; et al. (Supportive Care in Cancer, 2026)
Abstract Aim People with primary brain tumor (PBT) and their families experience high distress and face challenges navigating their disease and treatment, healthcare systems, and/or survivorship. Quality brain tumor care coordination (BTCC) enables continuous, timely care according to the individual care needs of patients. We aimed to explore healthcare professionals’ (HCPs) practices and perceptions of BTCC. Methods We conducted semi-structured interviews with 12 HCPs (92% female) working with people with PBT from Australia and Aotearoa New Zealand between June and November 2023. The median interview duration was 58 min. Qualitative data were analyzed thematically, with a framework matrix for data organization and systematic coding. Results Participants had a median of 13 years of experience in neuro-oncology across medical, nursing, and allied health disciplines, and reported experience in BTCC. We identified four themes related to BTCC: (1) Vulnerable and complex: Pervasive, multifaceted disabilities of PBT require specialist care; (2) Tailored coordination: Shaping and tailoring BTCC is in the best interests of patients and families; (3) Going the extra mile: Care needs warrant proactive support to mitigate crises; and, (4) Emotionally demanding: HCPs manage emotional load with limited support. Conclusion People with PBT experience a unique and complex set of care needs requiring specialist skills and knowledge beyond general oncology care coordination. BTCC encompasses continuous coordination of multidisciplinary care to optimize functioning for these individuals. Given the complexity of the BTCC role, better support infrastructure with training and resources, and appropriate interventions for HCPs are needed to retain HCPs and prevent burnout.